Turkey’s news media landscape in Twitter: Mapping interconnections among diversity - Doğu, Burak (Journalism, 2020)
Twitter plays a substantial role in shaping the online news media landscape, which is established on the interconnections between various actors. This research conducts network analysis in Twitter with the aim to explore Turkey’s polarized news media landscape in the aftermath of the Gezi protests. The findings, based on a relational approach, are analyzed at four levels: identifying the actors, positioning the actors and examining connections among their clusters, exploring the patterns of news diffusion, and reviewing media polarization. It has been found that distinct conditions such as intermedia differences apply to each one of those levels, while polarization is evident in the network.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDY0ODg0OTE3NzEzNzkx